Accurate solution estimates for vector difference equations - Rigoberto Medina (International Journal of Mathematics and Mathematical Sciences)
Accurate estimates for the norms of the solutions of a vector difference equation are derived. They give us stability conditions and bounds for the region of attraction of the stationary solution. Our approach is based on estimates for the powers of a constant matrix. We also discuss applications of our main results to partial reaction-diffusion difference equations and to a Volterra difference equation.